Dislocation of the proximal tibiofibular joint, do not miss it - van Wulfften Palthe, Alexander FY (BMJ Case Rep, 2015)
We present a case of a 45-year-old woman with a right proximal tibiofibular dislocation she sustained after a fall during roller skating. Anteroposterior and lateral radiographs confirmed the diagnosis; there were no other injuries. The dislocation was reduced by direct manipulation after intra-articular infiltration, in our emergency department. The patient was treated with a long, non-weight bearing leg cast for 1 week. After 4 weeks, she had no pain and a full range of motion of the knee.